EVALUATING TEACHER’S COMPETENCE IN DEVELOPING READING COMPREHENSION QUESTIONS BASED ON BARRETT’S TAXONOMY - Yude, Uswatun Hasanah; Zainil, Yetti (University of Kuningan, 2024)
This study investigates the competence of English teachers in developing reading comprehension questions based on Barrett's Taxonomy in Senior High Schools in Padang. Given the importance of effective questioning in stimulating critical thinking and comprehension, this research aims to assess the levels and types of questions formulated by teachers. Using cluster random sampling, 12 English teachers from 6 schools were selected. The study employed a test instrument to evaluate teachers' abilities to create questions across Barrett's five levels: Literal Comprehension, Reorganization, Inferential Comprehension, Evaluation, and Appreciation. Results indicate that most questions were at the Literal Comprehension level, with fewer questions addressing higher-order thinking skills (Evaluation and Appreciation). These findings highlight a need for professional development to enhance teachers' skills in crafting balanced and challenging questions.